Chemical Analysis of Urinary Stones - Ghanshyam Sigdel (Society of Surgeons of Nepal, 2016)
Introduction: Urinary stone disease is a common urological problem. Chemical analysis of the urinary stones is a part of metabolic evaluation of first time or recurrent stone formers. The report of chemical analysis of stones may obviate the need for complete metabolic evaluation or can direct metabolic evaluation. In this study we aim to find out the chemical compositions of urinary stones in our population, so that the result might serve as a baseline for the related research in future.